Radiological characterization of peloids obtained by maturation with Águas de Lindóia, Poços de Caldas and Peruíbe waters - Jefferson Koyaishi Torrecilha; Jussara Marques Oliveira Marrichi; Eduardo Aparecido Pirani de Souza; Paulo Flávio de Macedo Gouvêa; Isis Campos Alves; Allan Santos; Paulo Sergio Cardoso da Silva (Brazilian Journal of Radiation Sciences)
One of the concerns about using mineral clay for therapy treatments is its radioactivity content due to natural radionuclides, normally, associated with the clays. This work proposes to characterize the natural radionuclides of the peloids obtained by the maturation process of mixing two different clays (gray and green) with different mineral medicinal waters from Águas de Lindóia (SP), Poços de Caldas (MG) and sea water from Peruíbe (SP). The gamma spectrometry showed that the gray and green bentonite peloids, all the activity concentration of radionuclides are higher in gray ones, except 40K. The activity concentration varied from 84 to 156 Bq kg−1 (228Ra), 25 to 156 Bq kg−1 (228Th), 9 to 161 Bq kg−1 (226Ra), 39 to 256 Bq kg−1 (210Pb) and 162 to 1070 Bq kg−1 (40K). However, by calculating the absorbed dose rate in the worst scenario, this may not be a problem for topical application. Although the waters from Águas de Lindóia and Poços de Caldas are considered radioactive they have not caused a significant increase in radionuclide concentrations absorbed dose rate.